Research on weighting method of geological hazard susceptibility evaluation index based on apriori Algorithm - Chen, Bin; Wei, Na; Qu, Tianqiang; Zhang, Lianzhi; Li, Yingyi; Long, Xiao; Lin, Youxi (Frontiers in Earth Science, 2023)
Given the inconsistency between the information value and the weight value in the weighted information value model, a weight model based on the Apriori algorithm is established in this paper to analyze the correlation between the second-level intervals of disaster factors and the susceptibility of geological disasters. The objective weight of the second-level intervals of each index factor is calculated through the mining of association rules by the Apriori algorithm. The subjective uncertainty of the existing second-level factor weighting method is eliminated. Taking the geological disaster data of Xiangtan urban area as an example, 10 evaluation indexes were selected to establish the entropy weight method-information value model and entropy weight method-Apriori algorithm-information value model to evaluate the geological disaster susceptibility, and the disaster area ratio and ROC curve verification method were used to test and analyze the evaluation results. The results showed that compared with the entropy weight method-information value model, the entropy weight method-Apriori algorithm-information value model is used to evaluate the disaster area ratio of high-prone area increased by 58.3%, and the disaster area ratio of low-prone area decreased by 43.1%. The AUC value of the area under the ROC curve increased by 7.4%, and the evaluation accuracy was significantly improved compared with the former. This paper proves the rationality and practicability of the weighting method of the geological hazard susceptibility evaluation index based on the Apriori algorithm.